Artisanal fishing impact on deep coralligenous animal forests: A Mediterranean case study of marine vulnerability. (1st July 2019) - Enrichetti, F.; Bava, S.; Bavestrello, G.; Betti, F.; Lanteri, L.; Bo, M.
Abstract: Vulnerable Marine Ecosystems (VMEs) are characterized by prominent biological features susceptible to anthropogenic disturbances. Following international guidelines, the identification and protection of VMEs require a detailed documentation regarding both the community structure and the fishing footprint in the area. This combined information is lacking for the majority of the Mediterranean mesophotic rocky reefs that, similarly to deep-seabottoms, are known to host valuable animal forests. A deep coralligenous site exploited by artisanal fishermen in the NW Mediterranean Sea is here used as a model to assess the vulnerability of animal forests at mesophotic depths and evaluate the sustainability of artisanal fishing practices, particularly lobster trammel net. The Remotely Operated Vehicle (ROV) footage is used to document the biodiversity and health status of the megabenthic communities, while discard data are employed to quantify the entanglement risk, discard rates of fragile species and threats to sea floor integrity. A multidisciplinary approach is proposed for the assessment of the vulnerability criteria of an EU Special Area of Conservation, leading to specific management measures, including the delineation of fishing restrictions. Highlights: A multidisciplinary vulnerability assessment of a Mediterranean deep coralligenous site is carried out. ROV-Imaging and discard analysis are used to characterize benthic biocoenoses and to quantify fishing impact. High risk of entanglement leads to loss of structuring species and sea floor integrity. A valuable approach for VMEs identification over temperate mesophotic reefs is here proposed.